2021
DOI: 10.1134/s1063783421060160
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric and Ferroelectric Properties of Thin Heteroepitaxial Films of SBN-50

Abstract: The phase transformations and ferroelectric characteristics of thin films of barium-strontium niobate SBN-50 grown by RF-cathode sputtering in an oxygen atmosphere are studied using the dielectric spectroscopy and scanning probe microscopy (in the modes of force microscopy of the piezoresponse and Kelvin mode). It is shown that the films are characterized by a low surface roughness, an average size of ferroelectric domains ~100 nm, and spontaneous polarization directed from the substrate to the film surface. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Root-mean-square roughness of surface of the BNFNO film with a thickness of ∼ 1000 nm was 15.39 nm. The lateral size of grains was evaluated by the method of autocorrelation function [12] in a manner similar to [13]. The 2D-representation of the autocorrelation function, which was calculated in the analysis of the results of BNFNO film surface studies, is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Root-mean-square roughness of surface of the BNFNO film with a thickness of ∼ 1000 nm was 15.39 nm. The lateral size of grains was evaluated by the method of autocorrelation function [12] in a manner similar to [13]. The 2D-representation of the autocorrelation function, which was calculated in the analysis of the results of BNFNO film surface studies, is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The mean-square roughness of the film surface was 5.7 nm. For quantitative estimation of a lateral size of the grains, we have used the autocorrelation function method [16] similar to [17]. The 2D-representation of the autocorrelation function, which was calculated in the analysis of the results of the BNFNO film surface studies, is given in the Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thin films offer advantages including texturing of the materials, improvement of properties, and potential minimization of devices . For example, strain engineering with a proper choice of substrate and synthesis method can tune the properties of ferroelectric thin films. SBN thin films have been deposited by different synthesis methods, including PLD, RF sputtering, sol–gel synthesis, polymeric chemical method, , and chemical solution deposition (CSD) . The physical deposition techniques are time-consuming, hard to upscale, or expensive, while wet chemical synthesis often uses toxic organic solvents.…”
Section: Introductionmentioning
confidence: 99%